PELATIHAN CLOUD COMPUTING SEBAGAI PENYIMPANAN DATA BAGI SISWA(I) SMK KARTIKA MAKASSAR : CLOUD COMPUTING - samsuriah umar (Politeknik Negeri Sriwijaya, 2022)
The development of information technology in Indonesia has progressed a lot. This is also followed by the development of computer technology. The development of computer technology has a direct impact on the improvement of online learning carried out on students (i) in high school. The speed of technological development is one of the main needs to achieve the goals of students (i) and teachers or instructors. Cloud Computing is one option that is expected to help facilitate data storage. Cloud Computing can be used by students(i) especially in the current pandemic period learning that is still taking place online, such as learning and collecting assignments given by the teacher. The advantages of Cloud Computing have many advantages ranging from working alone to working together, fast in handling work and the procurement cost is not too expensive because it does not demand too high computer specifications, but affects the speed of access because it has to have internet access